2003
DOI: 10.1046/j.1365-2583.2003.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expression of a sterol carrier protein‐2 gene from the yellow fever mosquito, Aedes aegypti

Abstract: Trafficking of cholesterol in insects is a very important process due to the fact that insects depend on dietary cholesterol to fulfil their physiological needs. We identified a putative mosquito sterol carrier protein-2 (SCP-2) cDNA from fourth instar subtracted cDNA library. The AeSCP-2 protein has high degree homology in the sterol transfer domain to both rat and human SCP-2. Transcripts of AeSCP-2 in fourth instars were detected strongly in the midgut, and weakly in the head and hindgut. In the early pupae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
121
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(127 citation statements)
references
References 60 publications
5
121
0
Order By: Relevance
“…Only a few targeting molecules involved in cholesterol uptake/transportation are known in insects. Sterol carrier protein-2 (SCP-2) has been identified in several insect species 9,[30][31][32] and is thought to mediate cholesterol uptake and intracellular transportation. 9,11,12,33) Also, several chemical compounds that strongly inhibit the binding between cholesterol and AeSCP-2 (SCP-2 in Aedes aegypti) have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few targeting molecules involved in cholesterol uptake/transportation are known in insects. Sterol carrier protein-2 (SCP-2) has been identified in several insect species 9,[30][31][32] and is thought to mediate cholesterol uptake and intracellular transportation. 9,11,12,33) Also, several chemical compounds that strongly inhibit the binding between cholesterol and AeSCP-2 (SCP-2 in Aedes aegypti) have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The vertebrate SCP-2, SCP-x, and HSD17B4 have a peroxisome localization sequence in the C terminus, targeting these proteins to the peroxisome (1,2,4). The mosquito SCP-2 (AeSCP-2) appears to represent a unique nonperoxisomal and lowmolecular-weight protein in the SCP-2 gene family (5,6).…”
mentioning
confidence: 99%
“…Like the vertebrate SCP-2, AeSCP-2 binds cholesterol (5) and fatty acid (8). Similarly, both the vertebrate and AeSCP-2 increase cholesterol uptake in SCP-2-overexpressing cells (5,9). However, AeSCP-2 differs from the vertebrate SCP-2 in several aspects.…”
mentioning
confidence: 99%
“…A better understanding of the replication cycle of CHIKV in both insect cells and mammalian cells should help move forward in this fight [53] . Insects cannot synthesize cholesterol de novo and depend on dietary cholesterol for their physiological requirements [54] . Under culture conditions that allows to question the requirement for membrane cholesterol in C6/36 Aedes albopictus cells infected by CHIKV, we found that cholesterol depletion reduced the infectivity of strains bearing an alanine residue at position 226 of E1 (African CHIKV strain), whereas strains bearing a valine at position 226 of E1 (the Reunion Island CHIKV strain) are markedly less sensitive, indicating that the presence of valine represents a selective advantage for the virus subjected to this selection pressure [55] .…”
Section: Fight Against Health Threats: One Cannot Be Effective Againsmentioning
confidence: 99%